HIGH NPK SOLUTION AND PGP IMPROVED EOS PROPERTIES OF ROSE GROWN IN COCOPEAT - Dina M. Hameed,; Nazik H. Khalil, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This research was carried out at Research Station , Department of Horticulture and Landscape Engineering , College of Agricultural Engineering Sciences , University of Baghdad during fall season of 2020, it was aimed to improve flower productivity, quantity and quality of essential oils with increasing the concentration of N, P , K elements in the nutrient solution, and foliar app `lication of Plant growth promoters  (PGP) on Rosa Damascene grown on a soilless culture system with coco peat substrate bags. A factorial experimental design was carried out according to  (RCBD)with three replication. Results indicated the superiority of a high nitrogen treatment and 1.5 g of PGP (N2S2 ), of the flowers number, dry matter%, flower diameter, oil quantity and all physical and the anatomical characteristics, represented by the diameter of the head diameter of the glandular capillaries. Petals number increased significantly with a high potassium nutrient solution and PGP 1 g (N4S1).The high phosphorous solution, which was not treated with growth stimulator, showed superiority in the length of glandular capillaries.